A Review and Comparative Study of Existing Shrinkage Prediction Models for Portland and Non-Portland Cementitious Materials. (28th March 2016) - Ye, Hailong; Radlińska, Aleksandra
Abstract : This paper reviews shrinkage prediction models for cementitious materials and presents analysis of selected published data utilizing the aforementioned models. The main objective of this review is to revisit and reexamine the primary shrinkage mechanisms, that is, capillary pressure theory, Gibbs-Bangham shrinkage, and withdrawal of disjoining pressure in Portland and non-Portland cement. In particular, the theoretical basis for current shrinkage models is elaborated on and its soundness and applicability to explain the published experimental data are discussed. Additionally, a specific comparison was made among high water-to-cement (w/c) ratio ordinary Portland cement (OPC), low w/c OPC, and alkaline activated slag.